Disordered gambling among people with psychotic disorders: a systematic review - Anoop Sankaranarayanan; Preethi Ramanathan; Rinu Mathew; Helen Wilding; David Castle (Schizophrenia, 2024)
Abstract Disorders of gambling are more common among the mentally ill, including in people with psychotic disorders. The aim of this study was to conduct a systematic review of the literature regarding the prevalence and correlates of gambling disorders in people with psychotic disorders. We systematically reviewed English-language literature through searches of six bibliographic databases, all run on 11 November 2022: Medline ALL, Embase, Emcare, APA PsycINFO, CINAHL and the Cochrane Library. Observational studies that reported the prevalence of gambling in psychotic disorders or psychosis among gamblers were included. Studies were critically appraised using the Joanna Briggs Institute Critical Appraisal Tools. Sixteen studies, including 1,116,103 participants, from across a range of settings, were included. Most studies were done on males and recruited participants with a mean age of 40 years. Most of the studies (n = 12) were cross-sectional, and the remaining were case control in design. Most of the studies rated fair in quality. The prevalence of gambling among psychotic population ranged from 0.32 to 19.3%, with the majority of the studies reporting rates between 6.4 and 17%. The rates were 5–25 times higher than in the general population. While there were no consistent associations found with socio-demographic indices, several studies reported an association between gambling behaviours and substance use disorder among those with psychotic illnesses. Our research suggests that clinicians should assess for comorbid gambling among those with psychotic illness, particularly in those with mood symptoms, impulsivity, and substance use disorders. Gambling can negatively impact on their financial and social situations. Future research should study specific strategies or therapies among those with comorbid gambling and psychotic disorders.